A Comparative Study of Obstetric Outcome of Patients with Pregnancy Induced Hypertension - Ammara Mansoor, Tahira Akhtar, Ayesha Naeem, Samia Shafiq, Arifa Inayat, Firdous Ara (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Pregnancy-induced hypertension (PIH) is a common complication that affects maternal and fetal health. Objective: To assess and compare the obstetric outcomes in patients diagnosed with pregnancy-induced hypertension, including maternal complications, fetal health, and delivery outcomes. Methodology: This comparative study was conducted at Department of Gynaecology & Obstetrics, Gujranwala Medical College, Gujranwala from 1st January 2023 to 30th June 2023. A total of 320 patients were added in the study. Data were collected from hospital records, structured questionnaire and follow-up visits. The demographic and clinical data included patient age, parity, gestational age at diagnosis, obstetric history, and comorbid conditions. Results: Women with severe PIH had a higher incidence of complications such as preeclampsia (45% vs. 25%), placental abruption (15% vs. 5%), and stroke/acute renal failure (3% vs. 1%), and were more likely to undergo cesarean delivery (45% vs. 20%), with an average hospitalization duration of 6 days compared to 3 days for the mild PIH group. Fetal outcomes were also worse in the severe PIH group, with higher rates of intrauterine growth restriction (IUGR) (25% vs. 10%), preterm birth (18% vs. 8%), and lower average birth weight (2.7 kg vs. 3.1 kg). Neonates in the severe PIH group had lower Apgar scores, with 85% achieving a score of 7+ at 1 minute (compared to 95% in the mild PIH group), more frequent NICU admissions (20% vs. 6%), and higher rates of neonatal complications (25% vs. 7%). Conclusion: Severe pregnancy-induced hypertension is associated with higher maternal and fetal morbidity compared to mild PIH. Early diagnosis, close monitoring, and appropriate management are essential to reduce complications and improve obstetric outcomes in PIH patients. Keywords: Pregnancy-induced hypertension, maternal outcomes, fetal outcomes, preeclampsia, cesarean section, birth weight, preterm birth, NICU admissions.